2018
DOI: 10.1038/s41598-018-22156-5
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular trap-microparticle complexes enhance thrombin generation via the intrinsic pathway of coagulation in mice

Abstract: Abdominal sepsis is associated with dysfunctional hemostasis. Thrombin generation (TG) is a rate-limiting step in systemic coagulation. Neutrophils can expell neutrophil extracellular traps (NETs) and/or microparticles (MPs) although their role in pathological coagulation remains elusive. Cecal ligation and puncture (CLP)-induced TG in vivo was reflected by a reduced capacity of plasma from septic animals to generate thrombin. Depletion of neutrophils increased TG in plasma from CLP mice. Sepsis was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
124
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 111 publications
(138 citation statements)
references
References 60 publications
8
124
0
6
Order By: Relevance
“…We next asked if MPs attached to NETs play a role in NET‐induced inflammation. As shown recently (Wang et al, ), PMA stimulation of neutrophils triggers the formation of NETs containing numerous MPs (Figure a,c). Co‐incubation of neutrophils with calpain and caspase inhibitors resulted in the formation of NETs with markedly less MPs (Figure b,d).…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…We next asked if MPs attached to NETs play a role in NET‐induced inflammation. As shown recently (Wang et al, ), PMA stimulation of neutrophils triggers the formation of NETs containing numerous MPs (Figure a,c). Co‐incubation of neutrophils with calpain and caspase inhibitors resulted in the formation of NETs with markedly less MPs (Figure b,d).…”
Section: Resultssupporting
confidence: 84%
“…NETs are known to be loaded with numerous different nuclear, cytoplasmatic, and granular proteins, which contribute to the biological effects of NETs (Brinkmann et al, ). We have recently demonstrated that MPs formed during neutrophil activation can bind to NETs and form NET‐MP complexes, which are important for thrombin generation in sepsis (Wang et al, ). In the present study, we wanted to define the role of NET‐MP aggregates in the regulation of neutrophil recruitment in acute inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, c‐Abl kinase‐dependent generation of ROS might be involved in TNF‐α‐induced formation of NETs in neutrophils. Although neutrophil‐derived NETs are recognized for their important role in the innate immune system by trapping microbes facilitating microbiological clearance, several studies have shown that excessive formation of NETs is known to cause tissue injury and organ failure in infectious conditions . In this context, it is interesting to note that accumulating reports demonstrate that Abl kinase function is subverted by numerous bacterial and viral pathogens to achieve entry, motility, release, and survival in mammalian host cells .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor apoptotic vesicles may enhance the risk of thrombotic events in cancer patients undergoing chemotherapy by mechanisms depending notably on phosphatidylserine, TF expression, Factor VII and the prothrombinase complex . EV at large play an important role in the hypercoagulable state of cancer patients, and they have the potential to become involved in complexes with neutrophil extracellular traps, which lead to enhanced thrombin generation …”
Section: Effects Of Ev On Endothelial Cellsmentioning
confidence: 99%